2018
DOI: 10.1167/iovs.18-24504
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Deprivation Induces Dry Eye Through Inhibition of PPARα Expression in Corneal Epithelium

Abstract: PURPOSE. To determine if sleep deprivation induces dry eye through altering peroxisome proliferator-activated receptor alpha (PPARa) expression in mice. METHODS. The ''stick over water'' sleep deprivation-induced dry eye (SDE) model evaluated PPARa involvement in inducing this condition. Scanning electron microscopy (SEM) examined microvilli morphology in superficial corneal epithelial cells (SCECs) in SDE and PPARa À/À mice. Quantitative RT-PCR (qRT-PCR) and Western blot (WB) or immunostaining evaluated PPARa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 61 publications
(83 reference statements)
1
34
0
Order By: Relevance
“…PEA is an endogenous agonist of PPAR-a. In a previous study, we found that SD-induced declines in corneal PPAR-a expression result in increased corneal lipid accumulation (Tang et al, 2018). We also found that PPAR-a −/− mice have very similar corneal lipid accumulation compared to SDE mice.…”
Section: Ppar-a Mediates the Effect Of Pea On Sd-induced Lacrimal Damsupporting
confidence: 61%
See 2 more Smart Citations
“…PEA is an endogenous agonist of PPAR-a. In a previous study, we found that SD-induced declines in corneal PPAR-a expression result in increased corneal lipid accumulation (Tang et al, 2018). We also found that PPAR-a −/− mice have very similar corneal lipid accumulation compared to SDE mice.…”
Section: Ppar-a Mediates the Effect Of Pea On Sd-induced Lacrimal Damsupporting
confidence: 61%
“…PEA could not increase the tear production (B), reduce the LG (C) and acinar cell size (D), and ameliorate lipid deposition (E) in PPAR-a −/− mice. *, P < 0.05, **, P < 0.01 vs. control group, one-way ANOVA followed by Dunette's post hoc, n = 5. microvillus morphology, and severe LG lipid accumulation (Li et al, 2018;Tang et al, 2018). In clinical practice, use of artificial tears and anti-inflammatory eye drops is not a significant and effective treatment approach for these populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fenofibrate ameliorated the severity of ocular surface squamous metaplasia, commonly seen in patients with long-term deficiency of tear film [ 108 ] and suppressed the formation of tear film instability via the inhibition of macrophages and downregulation of pro-inflammatory factors [ 107 ]. In the corneal epithelium of mice with dry eyes by sleep deprivation, downregulation of PPARα expression was detected [ 109 ], and fenofibrate increased PPARα expression in cultured corneal epithelium sheets and restored microvilli morphology [ 109 ]. This implies PPARα activation could have potential for use as a preventive agent in patients with high risk of dry eye.…”
Section: Functions Of Pparα In the Eyementioning
confidence: 99%
“…Our earlier data indicate downregulation of PPAR-α expression in corneal epithelium of mice with dry eye induced by sleep deprivation. 18 However, further investigation is needed to elucidate the critical role of PPAR-α in the pathogenesis of dry eye and ocular surface squamous metaplasia. We hypothesized that activation of PPAR-α by agonists, such as fibrates, could alleviate squamous metaplasia by a mechanism similar to that of PPAR-γ.…”
mentioning
confidence: 99%